Behavior of granite-epoxy composite beams subjected to mechanical vibrations - Piratelli Filho, Antonio (2010)
The capacity to damp mechanical vibrations is one of the most important properties of granite-epoxy composites, even superior to the cast iron one. For this reason, these materials have been adopted for manufacturing of tool machine foundations and precision instruments. This work presents a study concerning the behavior of particulate composite beams, based on granite powder and epoxy, subjected to mechanical vibrations. Composite samples were prepared with different combinations of processing variables, like the weight fraction of epoxy in the mixture and size distributions of granite particles. The damping behavior of the material was investigated adopting the logarithmic decrement method. Samples, in the form of prismatic beams, were excited in the middle point and the output signal was measured in a point located at the extremity. The obtained results showed that composite samples, with weight fractions of about 80% of granite and 20% of epoxy, presented damping properties approximately three times greater than gray cast iron.